2003
DOI: 10.1289/ehp.5945
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of p53 protein in A549 human pulmonary epithelial cells exposed to asbestos fibers.

Abstract: We examined effects of asbestos exposure on the phosphorylation of p53 protein in human pulmonary epithelial type II cells (A549), which express wild-type p53. In cells exposed to two different types of asbestos, chrysotile (approximately 1-6% iron content) and crocidolite (approximately 27% iron content) fibers, at the doses of 1, 5, and 10 microg/cm2 for 24 hr, the levels of p53 phosphorylated at Ser15 and p53 protein were correlated with the dose. On a per-weight basis, chrysotile was more potent in inducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 48 publications
0
14
1
Order By: Relevance
“…Collectively, these data suggest a novel mechanism involving mitochondrial-derived ROS in mediating amosite asbestosinduced p53 expression and subsequent AEC apoptosis by the intrinsic pathway. In contrast to the findings presented here, Matsuoka and colleagues (33) showed that chrysotile asbestos increases p53 protein accumulation in A549 cells due to phosphorylation of serine 15 by phosphatidylinositol 3-kinase related kinase family member, such as ataxia-telangiectasia mutated kinase. Further, they found that this was not blocked by catalase, deferoxamine, or N-acetylcysteine, suggesting that p53 stabilization by Figure 6.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Collectively, these data suggest a novel mechanism involving mitochondrial-derived ROS in mediating amosite asbestosinduced p53 expression and subsequent AEC apoptosis by the intrinsic pathway. In contrast to the findings presented here, Matsuoka and colleagues (33) showed that chrysotile asbestos increases p53 protein accumulation in A549 cells due to phosphorylation of serine 15 by phosphatidylinositol 3-kinase related kinase family member, such as ataxia-telangiectasia mutated kinase. Further, they found that this was not blocked by catalase, deferoxamine, or N-acetylcysteine, suggesting that p53 stabilization by Figure 6.…”
Section: Discussioncontrasting
confidence: 99%
“…phosphorylation of serine 15 can occur by mechanisms that are independent of ROS production. Although ataxia-telangiectasia mutated kinase is implicated in mediating mitochondriaregulated apoptosis by radiation (34), the role of phosphorylation of serine 15 on p53 in mediating apoptosis was not examined in this study (33). A hypothetical model depicting the oxidantdependent and oxidant-independent mechanisms by which asbestos affects p53 expression and apoptosis is shown in Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we investigated the role of p53 on KLF17 regulation in A549 cells. A549 cell lines express tumor-suppressive p53 (TP53) (34,35). We depleted p53 expression in A549 cells using specific siRNA targeting p53.…”
Section: Resultsmentioning
confidence: 99%
“…Altered p53 expression has been implicated in the pathophysiology of pulmonary fibrosis, including that due to asbestos, as well as asbestos-associated malignancies, especially bronchogenic lung cancer (Nelson et al, 2001;Mishra et al, 1997;Burmeister et al, 2004;Plataki et al, 2005). Asbestos activates p53 and p21 expression in lung epithelial and mesothelial cells that result in cell cycle arrest (Levresse et al, 1997;Matsuoka et al, 2003;Kopnin et al, 2004). Furthermore, increased p53 levels are detected in lung cancers of patients with asbestosis (Nuorva et al, 1994) and p53 point mutations are present in the lung epithelium of smokers and asbestosexposed individuals (Husgafvel-Pursiainen et al, 1997).…”
Section: P53 and Mitochondrial Dna Repairmentioning
confidence: 99%